GROSS DOMESTIC PRODUCT, EDUCATION, UNEMPOYMENT AND POVERTY: EVIDENCE FROM SOUTH SUMATERA PROVINCE, INDONESIA - Muhammad Yusuf (LPPM UNIVERSITAS BINA INSAN, 2020)
This study determine the effect of Gross Domestic Product (GDP), education level and unemployment rate on the poverty in the South Sumatra Province in year of 2013 – 2018. The method uses panel data analysis using Eviews program with combination time-series data and cross-section data using panel data through fixed effects Model. The data obtained from the Central Statistic Bureau of Indonesia. The results showed that the GDP variable and the education level are negative and significant effect on poverty in the South Sumatra Province, the unemployment level is positive and significant effect on poverty in the South Sumatra. The information and the policy considerations related parties to improve the system of growth and development in the South Sumatra especially, and Indonesia in general.